Odpowiedzi

2010-02-19T09:46:29+01:00
A) x=? x=2/3h a=6
y=? y=1/3h h=6pierwiastek z 3 /2
h=3pierwiastek z 3

x=2/3*3 pierwiastek z 3
x=2 pierwiastek z 3
y=1/3 * 3 pierwiastek z 3
y=pierwiastek z 3

b)H=?
a=3
k=5

a=3
x=2/3h
h=3pierwiastek z 3/2
x=pierwiastek z 3

H2+x2=k2
H2+(pierwiastek z 3)2=5<do kwadratu>
H2+3=25
H2=25-3
H2=22
H=pierwiastek z 22

c)x=2pierwiastki z 3
c=?
H=4
x=2/3h
y=1/3h
x=2pierwiastek z 3
y=pierwiastek z 3
4<do kwadratu> +(pierwiastek z 3)2=c2
16+3=c2
c2=19c=pierwiastek z 19

d)
H2+x2=k2
(2pierwsiatki z 13)2 +x2=10<do kwadratu>
52+x2=100
x2=100-52
x2=48
x=4pierwiastek z 3

x=2/3h
4pierwiastek z 3 =2/3h
h=4pierwaistek z 3 / 2/3
h=6 pierwiastek z 3
6 pierwiastek z 3=a pierwiastek z 3/2
12pierwaistek z 3= a pierwiastek z 3
a=12 pierwiastek z 3 /pierwiastek z 3
a=12







9 3 9